Impact of education and income inequalities on life expectancy: insights from the new EU members - Sart, Gamze; Bayar, Yilmaz; Danilina, Marina (Frontiers in Public Health, 2024)
Life expectancy is one of the primary population health indicators and in turn increases in life expectancy indicate improvements in population health and human welfare. Therefore, one of the ultimate goals of the countries is to increase the life expectancy. This article studies the effect of education and income inequalities, ICT indicators, CO2 emissions, and real GDP per capita on life expectancy in the new EU members for the period of 2010–2022 by employing fixed effects regression. The coefficients of panel regression uncover that education and income inequalities and CO2 emissions negatively impact life expectancy, but ICT indicators of internet usage and mobile cellular subscriptions and real GDP per capita positively affects the life expectancy. The findings of the panel regression analysis indicate that public policies to decrease the inequalities in education and income will make a contribution to life expectancy.